2018
DOI: 10.1007/978-3-319-99670-7_46
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Decision-Making Against Induced Seismicity in Deep Fluid Injections

Abstract: The rise in the frequency of anthropogenic earthquakes due to deep fluid injections is posing serious economic, societal, and legal challenges to geoenergy and waste-disposal projects. We propose an actuarial approach to mitigate this risk, first by defining an autonomous decision-making process based on an adaptive traffic light system (ATLS) to stop risky injections, and second by quantifying a "cost of public safety" based on the probability of an injection-well being abandoned. The ATLS underlying statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…McGarr has shown that this relationship is consistent with the data from a compilation of injections. However, a number of researchers (Gischig et al, 2014;van der Elst et al, 2016;Mignan et al, 2019b) have pointed out that outliers exist (e.g., Pohang, South Korea - Grigoli et al, 2018, andKim et al, 2018;St. Gallen, Switzerland -Diehl et al, 2017) and that the Mc-Garr limit is best explained as a purely statistical relationship based on simple extreme-value-theory principles (Embrechts, 2013).…”
Section: Upper Bound For the Gutenberg-richter Distribution Vs Maximum Observed Magnitude Distributionmentioning
confidence: 99%
“…McGarr has shown that this relationship is consistent with the data from a compilation of injections. However, a number of researchers (Gischig et al, 2014;van der Elst et al, 2016;Mignan et al, 2019b) have pointed out that outliers exist (e.g., Pohang, South Korea - Grigoli et al, 2018, andKim et al, 2018;St. Gallen, Switzerland -Diehl et al, 2017) and that the Mc-Garr limit is best explained as a purely statistical relationship based on simple extreme-value-theory principles (Embrechts, 2013).…”
Section: Upper Bound For the Gutenberg-richter Distribution Vs Maximum Observed Magnitude Distributionmentioning
confidence: 99%
“…many uncertainties associated with the process of inducing seismicity and the needs of regulators, insurance and the public (Mignan et al, 2019a;2019b). Both hazard and risk approaches follow standards proposed, among others, by the Swiss Seismological Service (SED, 2017) and related references (Broccardo et al 2017a, Mignan et al, 20152019a;b), which are based on a combination of Probabilistic Seismic Hazard Analysis (PSHA) and the PEER-PBEE framework (Cornell, 1968;Cornell, Krawinkler, 2000).…”
Section: Probabilistic Fluid-induced Seismic Hazard Assessmentmentioning
confidence: 99%
“…Adding an additional concern, deep geothermal projects in Europe-and the Geldinganes stimulation is no exception-are often located close to consumers, thus in densely urbanized areas with historical and hence vulnerable buildings and infrastructures. In these contexts, the problem of assessing and managing induced seismicity is especially important (Mignan et al, 2015;2019a;2019b). It is also a well-known fact that societal acceptance of https://doi.org/10.5194/nhess-2019-331 Preprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Seismogenic Index is a simple yet robust model that relies on a linear relationship between volume rate and seismicity rate, and has proven its reliability in numerous induced seismicity sequences (Mignan et al, 2017(Mignan et al, , 2021Shapiro et al, 2010). Recent work showed that its parameters can be updated in near real time during stimulations (Broccardo et al, 2017(Broccardo et al, , 2019Mignan et al, 2019). The Epidemic-Type Aftershock Sequence model relies on several empirical observations, from the Gutenberg-Richter power law, to Omori's law for aftershock decay.…”
Section: Introductionmentioning
confidence: 99%